DHA-1-producing Klebsiella pneumoniae in a teaching hospital in the Czech Republic - Empel, Joanna; Hrabák, Jaroslav; Kozińska, Aleksandra; Bergerová, Tamara; Urbášková, Pavla; Kern-Zdanowicz, Izabela; Gniadkowski, Marek (Microbial drug resistance (Larchmont, N.Y.), 2010)
Thirty-eight AmpC-producing Klebsiella pneumoniae isolates identified from January to October 2006 in a large teaching hospital in the Czech Republic were analyzed. The AmpC cephalosporinase was identified as DHA-1, encoded by a plasmid-located complex class 1 integron, previously observed in a K. pneumoniae isolate from the Parisian region. The DHA-1 expression was inducible, and although in two isolates with higher resistance, the induction effect was masked at the phenotypic level. All of the isolates belonged to the international K. pneumoniae clone sequence type 11, split into two disseminated pulsed-field gel electrophoresis types. This is the first report on enterobacteriaceae with acquired AmpCs in the Czech Republic and possibly the first description of organisms with DHA-1 in the Central and Eastern Europe.
Keywords: Klebsiella Infections; Plasmids; infekce bakteriemi rodu Klebsiella; Bacterial Proteins; Electrophoresis, Gel, Pulsed-Field; Česká republika; pulzní gelová elektroforéza; antibakteriální látky; Integrons; beta-Lactamases; integrony; Microbial Sensitivity Tests; nemocnice fakultní; Klebsiella pneumoniae; beta-laktamasy; Czech Republic; lidé; Anti-Bacterial Agents; Humans; mikrobiální testy citlivosti; bakteriální proteiny; plazmidy; Hospitals, Teaching